Spigelian hernia: rare so, beware! - George, Robinson; MS, Vasanthi; Prasad, K.; Prasad, Arun (International Surgery Journal, 2016)
Spigelian Hernia (SH) is a type of interparietal abdominal wall hernia which is usually present at the level of the arcuate line in the area of ‘Spigelian belt’. Hardly, 1000 cases have been reported in surgical literature of which an acute presentation is rarely seen. Hence, we report this case which is an acute variant of Spigelian hernia, with a review of literature to discuss the diagnostic factors and treatment, as such kind of hernias are elusive clinically with fatal outcome, if ignored.